Design and Implementation of an Outdoor Line Follower Robot for RoboCup Search and Rescue League - Dilaver, Mustafa Burak; Uslu, Erkan; Cakmak, Furkan; Altuntas, Nihal; Amasyali, M. Fatih; Yavuz, Sirma (IEEE, 2017)
RoboCup is the most prestigious robotics contest in the world, with increasing popularity among robot communities and new contests. In this study, design and implementation of a line follower robot for outdoor categories which have been recently added to RoboCup Search and Rescue League is emphasized. In this category, a 100m long colored rope is placed in a field whose floor is made of sand, concrete and laminate and the competing robots are ranked according to the maximum trajectory distance that they cover in 20 minutes. The track is made of right and acute angle parts for the robot which is expected to follow the line including also 15. ramps. The robot which is implemented on ROS (The Robot Operating System) follows the line with the camera sensor above it.
Keywords: RoboCup Search and Rescue League; outdoor category; line follower robot; Acoustics; Computer Science; Engineering; Telecommunications